2003
DOI: 10.1063/1.1605794
|View full text |Cite
|
Sign up to set email alerts
|

Super-resolution by elliptical bubble formation with PtOx and AgInSbTe layers

Abstract: The recording and retrieval of signals below 100 nm mark length were attempted with elliptical bubble-type super-resolution technology with platinum oxide (PtOx) and ductile AgInSbTe layers, using the same optical system as that of a digital versatile disk (a 635 nm wavelength red laser system). The carrier-to-noise ratio (CNR) of over 47 dB for 100 nm mark length signals (over 43 dB for 80 nm mark length signals) was obtained, which can be considered as a commercially acceptable level of CNR. The recording me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
75
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 14 publications
1
75
0
Order By: Relevance
“…With the development of the phase-change memory, various materials were examined, and the materials of the best performances in terms of speed and stability were found to be GeSbTe (abbreviated as GST) family, such as Ge 2 Sb 2 Te 5 and Ge 1 Sb 4 Te 7 [4,9,16,17,[21][22][23], and AgInSbTe (abbreviated as AIST) family, such as Ag 3.4 [2,3,7,[11][12][13][14][15][24][25][26][27][28]. The thermal properties of GST family were measured and studied in details, and the studies showed that there were common characteristics for different members in the GST family due to the distorted NaCl-type rock structures [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the development of the phase-change memory, various materials were examined, and the materials of the best performances in terms of speed and stability were found to be GeSbTe (abbreviated as GST) family, such as Ge 2 Sb 2 Te 5 and Ge 1 Sb 4 Te 7 [4,9,16,17,[21][22][23], and AgInSbTe (abbreviated as AIST) family, such as Ag 3.4 [2,3,7,[11][12][13][14][15][24][25][26][27][28]. The thermal properties of GST family were measured and studied in details, and the studies showed that there were common characteristics for different members in the GST family due to the distorted NaCl-type rock structures [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…When the laser beam is switched off, the melted marks quench into an amorphous state due to the high thermal conductivity of the substrate underneath the phase-change materials. Conversely, the recorded marks are erased when the materials are heated above the glass transition temperature but yet below the melting threshold so that the materials return to the crystalline state [7][8][9][10][11][12][13][14][15][16][17]. For the nonvolatile electrical storage, applying a higher voltage pulse (reset pulse) to the crystalline state with low resistivity leads to the local melting and consequently the formation of an amorphous information bit with high resistivity due to the rapid quenching.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the 100 nm recording marks in the track direction were realized, and the mark size corresponds to 1/10 of the laser spot size (∼1.0 um). Figure 8.19 presents the experimental results from [20], and Fig. 8.19a is the dependence of CNR on mark size.…”
Section: Recordable Super-resolution Optical Disks With Nonlinear Revmentioning
confidence: 98%
“…In the bubble-type marks, the Pt particles can enhance the readout signal and improve the CNR of dynamic readout. In order to demonstrate the schematics, Kim et al carried out the dynamic recording and readout by using Pulstec DDU-1000 with a laser wavelength of 635 nm and a lens with an NA of 0.60 [20]. The disks were rotated at a velocity of 6.0 m/s.…”
Section: Recordable Super-resolution Optical Disks With Nonlinear Revmentioning
confidence: 99%